Steri-stripTM versus subcuticular skin closure of paediatric groin wounds: A randomised study - Oluwaseun Abiola Ladipo-Ajayi; Taiwo Akeem Lawal; Olukayode O Ogundoyin; Afieharo Igbibia Michael (Wolters Kluwer Medknow Publications, 2022)
Background: A technique that offers the best chance of an optimal result is most appropriate to be employed for wound closure. Aims: We set out to compare the cosmetic outcome, and wound complication rates associated with clean paediatric groin wounds closed using Steri-Strip™ or subcuticular suturing. Settings and Design: A prospective randomised study. Subjects and Methods: Children of African descent with unilateral and bilateral clean groin wounds were randomised into subcuticular suture skin closure and Steri-Strip™ groups and followed up postoperatively. Cosmetic assessment and outcome were scored based on parents' satisfaction using the visual analogue scale (VAS) and a single Plastic Surgeon assessed pictures of the scars using the Hollander Wound Evaluation Scale (HWES). Statistical analysis was used SPSS version 18. Results: Seventy-five wounds were assessed, (n = 35, Steri-Strips™) and (n = 40, suturing). Closure with Steri-Strips resulted in scars with comparable cosmesis as those with subcuticular suturing. Wound complications were also similar. There was no statistically significant difference between mean VAS scores on the 5th day (P = 0.320), 2nd week (P = 0.080), 4th week (P = 0.070) and 8th week (P = 0.080). The HWES scores were also comparable at those times. Conclusions: We conclude that skin closure of clean paediatric groin wounds with SteriStrips™ gives comparative cosmetic outcomes with subcuticular suturing.